2021
DOI: 10.35869/vial.v0i18.3363
|View full text |Cite
|
Sign up to set email alerts
|

Classroom enjoyment and anxiety among Saudi undergraduate EFL students: does gender matter?

Abstract: The current study was motivated by recent interest in the effect of positive and negative emotions in the context of foreign language learning resulting from the rise of the positive psychology movement (Dewaele & MacIntyre, 2016; MacIntyre & Mercer, 2014). It examines the construct of foreign language enjoyment (FLE) and its relationship with foreign language classroom anxiety (FLCA) among a group of 487 English as a foreign language (EFL) students (340 females, 147 males) enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
3
16
2
Order By: Relevance
“…It is well-recognized and wellestablished that foreign language anxiety plays a negative role in foreign language learners' progress and performance (Liu and Jackson, 2008;MacIntyre and Gregersen, 2012;MacIntyre and Mercer, 2014;MacIntyre and Vincze, 2017;MacIntyre et al, 2019). Dewaele and Alfawzan (2018) and Bensalem (2021) further confirmed such a negative relationship between anxiety and foreign language achievement. Besides, by analyzing a group of 189 foreign language pupils and 152 English learners and users in Saudi Arabia, they discovered that better test results were obtained when students had higher levels of enjoyment in foreign language classes.…”
Section: Research On Esp Writing and The Influence Of Emotions On Lan...mentioning
confidence: 78%
“…It is well-recognized and wellestablished that foreign language anxiety plays a negative role in foreign language learners' progress and performance (Liu and Jackson, 2008;MacIntyre and Gregersen, 2012;MacIntyre and Mercer, 2014;MacIntyre and Vincze, 2017;MacIntyre et al, 2019). Dewaele and Alfawzan (2018) and Bensalem (2021) further confirmed such a negative relationship between anxiety and foreign language achievement. Besides, by analyzing a group of 189 foreign language pupils and 152 English learners and users in Saudi Arabia, they discovered that better test results were obtained when students had higher levels of enjoyment in foreign language classes.…”
Section: Research On Esp Writing and The Influence Of Emotions On Lan...mentioning
confidence: 78%
“…The low social status also limits their interaction with people. Therefore, the effect of gender on anxiety may be neutralized and show no significant differences [19].. However, the research on Korean participants show significant differences with females more intense emotion .Korean culture also resemble male-dominated culture.…”
Section: 2discussion On Researches Of Flca and Gendermentioning
confidence: 92%
“…As a reflection on the three mentioned studies, Bensalem's finding suggests there was no significant difference between intensity of anxiety among male and female learners except two questionnaires items in relation to speaking in class shown significant gender [19].Dewaele observed female leaners with both significant more positive and more mild negative emotions. Women's heightened emotionality may benefit the acquisition and production of the FL [17].…”
Section: 2discussion On Researches Of Flca and Gendermentioning
confidence: 93%
“…In these circumstances, the new university environment after high school could play a significant role in females' use of English in communication. In a recent study, Bensalem (2021) found that female students felt significantly more anxious in English, even though they were well prepared. Apart from that, it is extremely important to encourage freshmen females to actively express their views and questions in English with their peers and professionals.…”
Section: Discussionmentioning
confidence: 94%